PENYELESAIAN PERSELISIHAN AKIBAT PEMUTUSAN HUBUNGAN KERJA (PHK) SEPIHAK OLEH PT HUNG A INDONESIA - Jonathan Jordan Sianipar; Radifya Indri Safinka; Sisca Mustika Tiara; Osmar Fawwaz Hasrianda Syah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The unilateral termination of employment (PHK) by PT Hung A Indonesia has caused serious problems in industrial relations in Indonesia, involving more than a thousand affected workers. This study aims to analyze the dispute resolution mechanism due to unilateral layoffs and legal protection for workers. The research method used is descriptive analytical, with data collection through interviews and related documents. The results showed that despite recommendations from the mediator to provide compensation in accordance with the Collective Labor Agreement (CLA), the company management refused to implement the recommendations, thus creating uncertainty and dissatisfaction among workers. This study recommends the need for increased legal awareness among workers and stricter law enforcement against violations of workers' rights.